IMPLEMENTASI KEGIATAN HOME HEALTH PROMOTIONDALAM PROGRAM KETUK PINTU LAYANI DENGAN HATI (KPLDH) PEMERINTAH PROVINSI DKI JAKARTA DI KECAMATAN KEBAYORAN LAMA, JAKARTA SELATAN - Umboh, Riane Olviyobel; Fawzi, Indra Lestari (UI Scholars Hub, 2020)
Ketuk Pintu Layani Dengan Hati (KPLDH) is a health program from the Government of DKI Jakarta that has been planned and executed since 2015. This program aims to make health access near to the people, especially middle to lower class. In this program, a health team (consists of 3 medical personnel: doctor, midwife, and nurse) visits people’s homes. This research focuses to one of the program’s implementations: Home Health Promotion, which aims to educate people to have a health paradigm in Kecamatan Kebayoran Lama District. Among other districts in South Jakarta, statistically this district is the most densely populated with high numbers of newcomers. Also, the accomplishment of the KPLDH program in this district is the lowest among others. This research focus to describe the implementation of Home Health Promotion, and to discover supporting and obstacle factors of the implementation of its activity using qualitative approach with data collection technique using field observation and in-depth interview to the program’s planner, executors, and recipients. The result of this research shows that health promotion holds an important role in people’s empowerment in the health field. The main supporting’s factors of this programme are from Head of the Puskesmas and positive response from the beneficiaries, while the obstacles of this programme are limited budget, lack of human resources, and lack of work’s facilities.